Do Shia-Sunni Tensions Affect Iranian-Saudi Relations? - M. A. Podrezov (Концепт: философия, религия, культура, 2023)
Today the rivalry between Iran and Saudi Arabia is one of the defining factors in the Middle East political arena. The Islamic world's division into Shiite and Sunni is often considered a factor affecting bilateral relations between Tehran and Riyadh. Iran positions itself as the center of gravity for all the Shiites in the region, while Saudi Arabia seeks to form an anti-Iranian alliance on a Sunni basis. This article assesses the impact of the doctrinal tensions between these two branches of Islam on the Iranian approach towards its relations with Saudi Arabia. For this purpose, the author analyses the rhetoric of Iranian officials, clerics, and state-run media in the context of the main concepts of the Iranian contemporary religious ideology. The author concludes that criticism of Saudi Arabia has lost its religious connotation and Tehran does not position its confrontation with Riyadh as a fight against the enemies of Islam or apostates. The traditional epithets classifying their holders as supporters of the forces of darkness and actively used against the Western countries and Israel are not cited by critics of the Saudi dynasty. Moreover, the criticism of Wahhabism as a religious movement is not linked to the kingdom's current political leadership. On the contrary, the Iranian criticism of the Saudi foreign and domestic policies focuses on condemning the Saudi authorities' infringement on human rights and media freedom, supporting the protest movement in Iran, and fighting the Houthis. Even the persecution of Shiites in Saudi Arabia, to which the Iranian press has devoted considerable attention, is viewed from the perspective of the global concept of human rights, rather than as the struggle of one religious group against another. The kingdom itself is not considered an ideological enemy of Iran, which since the Islamic Revolution has been the US and Israel. The statements by some representatives of the Iranian political establishment on the need for peaceful coexistence between the two countries, along with the March 2023 agreements on normalizing bilateral relations indicate Tehran's pragmatic approach to interaction with Riyadh which is not affected by the ShiaSunni controversy in its dogmatic and religious dimensions.